ANALISIS HARGA, PROMOSI, SALESMAN, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA VARIO 125 ( PT. NAGA MAS MOTOR POS CEMANI) - Tarochma Anggun Mei Candra; Supawi Pawenang; Djumali Djumali (ITB AAS INDONESIA Surakarta, 2020)
The purpose of this research is to find out how big an influence, price, promotions, the salesman and the location of the purchase. The results of this study explain that hypothesis testing 1 i.e. the price the positive effect of purchase supported by empirical evidence. Hypothesis testing 2 indicates that the promotion of the potential negative effect against the purchasing decision. Hypothesis testing 3 explains that the salesmen did not influence on purchasing decisions. The results of hypothesis testing 4 indicates that the location does not have an effect on purchasing decisions. Keywords: Price, Promotion, Salesman, Location,Purchase Decisions